Solanum surrattence as Potential Corrosion Inhibitor. (28th August 2012) - Sharma, Manish Kumar; Sharma, Anil Kumar; Mathur, S. P.
Abstract : Developping chip and ecofriendlly corrosion inhibitors can replace toxic chemicals which are currently used in industries. Plant extract of Solanum surrattence in acetone, petroleum ether, and methanol has been tasted using mass loss and thermometric measurements for corrosion of aluminium in acid solutions. The plant extract of Solanum surrattence is a good corrosion inhibitor for aluminium. The inhibition efficiency depends upon the concentration of inhibitors, it inhibits the metal of 97.60% at its maximum value. This inhibitor shows efficiency at 25°C. At higher temperature the inhibition efficiency decreases. These types of inhibitors can be used to replace the toxic chemicals which are currently used in industries. We find out cheap and ecofriendlly corrosion inhibitors which can be used by acid, petrochemical, and chemical industries.